1982
DOI: 10.1161/01.str.13.5.641
|View full text |Cite
|
Sign up to set email alerts
|

Predicting functional outcome following acute stroke using a standard clinical examination.

Abstract: SUMMARY In a series of 149 patients admitted to a stroke unit, the outcome of the acute phase of stroke rehabilitation, assessed by the patients' return to independence, was found to be related to the results of standardized weekly clinical examinations of mental, motor, sensory and communication function. The prediction of subsequent independence was estimated just as accurately using the results from three of these tests (upper limb motor function, postural function and proprioception) as when using the enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(109 citation statements)
references
References 10 publications
4
104
0
1
Order By: Relevance
“…Candidate determinants for development of a prediction model included the following: (1) (11) sensory deficit in the arm as determined by the Thumb-Finding Test (0 to 3 points); 17 (12) Orpington Prognostic Score (1.6 to 6.8 points); (13) homonymous hemianopia 18 (noϭ0/yesϭ1); (14) inattention (1 if Ͼ2 omissions on the letter-cancellation test); 18 (15) conjugate gaze 19 (noϭ0/yesϭ1); (16) social support (noϭ0/yesϭ1); (17) type of (additional) therapy (air splint, arm, or leg training; 0 to 2) 8 ; and (18) severity and extent of paresis of upper and lower extremity motor function in arm and leg as assessed by the Motricity Index (MI) 20 and motor parts of the Fugl-Meyer (FM) score. 21 In the MI, muscle strength was measured for upper extremity (MI arm, 0 to 100) in which 100 points represents normal strength and lower extremity (MI leg, 0 to 100) separately, whereas FM motor scores were subdivided into FM arm score (including wrist, 0 to 52), FM hand score (0 to 14 points), and FM leg score (0 to 34 points) in which the maximum score represents no synergism.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Candidate determinants for development of a prediction model included the following: (1) (11) sensory deficit in the arm as determined by the Thumb-Finding Test (0 to 3 points); 17 (12) Orpington Prognostic Score (1.6 to 6.8 points); (13) homonymous hemianopia 18 (noϭ0/yesϭ1); (14) inattention (1 if Ͼ2 omissions on the letter-cancellation test); 18 (15) conjugate gaze 19 (noϭ0/yesϭ1); (16) social support (noϭ0/yesϭ1); (17) type of (additional) therapy (air splint, arm, or leg training; 0 to 2) 8 ; and (18) severity and extent of paresis of upper and lower extremity motor function in arm and leg as assessed by the Motricity Index (MI) 20 and motor parts of the Fugl-Meyer (FM) score. 21 In the MI, muscle strength was measured for upper extremity (MI arm, 0 to 100) in which 100 points represents normal strength and lower extremity (MI leg, 0 to 100) separately, whereas FM motor scores were subdivided into FM arm score (including wrist, 0 to 52), FM hand score (0 to 14 points), and FM leg score (0 to 34 points) in which the maximum score represents no synergism.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Previous investigators have shown that a single model can be applicable to patients seen at any time up to 30 days from stroke onset. 12 The models were developed on 530 of the original 675 patients: 54 patients were excluded because they were not assessed by a study neurologist (50 died before they could be assessed), 58 were seen after 30 days, and 33 had a subarachnoid hemorrhage (SAH).…”
Section: Description Of Training Data Setmentioning
confidence: 99%
“…Other studies have shovra that cognitive performance (e.g. memoty, orientation and absttact thought) is associated with success of rehabilitation (Stahelin, 2000;Prescott et al, 1982) and reintegration into the community (Neistadt, 1987).…”
Section: Patient Characteristics and Cognitive Impairmentmentioning
confidence: 99%